Unrealistische Einnahmeplanung durch Geber und Nehmer: Das Beispiel Bremen - Ernst Mönnich (Wirtschaftsdienst, 2013)
Die Haushaltsnotlage Bremens ist bereits chronisch. Sie wurde immer wieder mit Sanierungsprogrammen bekämpft, allerdings gingen die Gestalter dieser Programme regelmäßig von einem übertrieben optimistischen Einnahmewachstum aus. Tatsächlich kam es dann aber in der Regel nicht zu einer positiven Entwicklung. Der Autor mahnt eine realistischere Einahmeplanung für die künftige Infrastruktur- und Steuerpolitik an. – – A long-term analysis of incorrect revenue forecasts for the state of Bremen shows the importance of these forecasts for the failure of budgetary rehabilitation programmes. The findings contradict those analysts who blame misleading incentives in the federal distribution system of common taxes and advocate expenditure cutting. Looking forward, this development may reoccur, not only in Bremen but in other states as well, which would jeopardise the constitutional limit on deficits. This paper discusses the fiscal policy conclusions to draw from this unrealistic planning, addressing both the problems of states in a budgetary crisis and the system of tax distribution in Germany, which has to be reorganized in 2020.
Keywords: H63; H64; H77; 330; Haushaltsdefizit; Steuereinnahmen; Bremen (Land)